(untitled) (The Planet, 2024)
Background: Primary Open-Angle Glaucoma (POAG) is a leading cause of irreversible blindness, often with no early symptoms. This study examined age and gender differences in POAG prevalence among people with Type 2 Diabetes to support better screening in high-risk groups. Methods & Materials: This cross-sectional analytical study was conducted at the Department of Ophthalmology in collaboration with the Department of Endocrinology, BIRDEM General Hospital, Dhaka, from March 2022 to April 2023. The study population comprised 185 type 2 diabetic patients in total. Patients either admitted or attending OPD at the Department of Ophthalmology & Endocrinology OPD of BIRDEM General Hospital, Dhaka was included in this study. Statistical analysis was performed using SPSS version 27.0. A p-value of ≤0.05 was considered statistically significant. Result: The study found that the mean age of respondents was 51.6 ± 6.6 years, with a higher proportion (53.5%) in the 51-60 years age group. There was a significant difference in age between the POAG group (54.2 ± 6.06 years) and the normal group (51.03 ± 6.6 years, p = 0.013). Males were more prevalent in the POAG group (53.1%) compared to the normal group (30.7%, p = 0.031). Conclusion: The study finds that older age and male gender increase the risk of Primary Open-Angle Glaucoma (POAG) in people with Type 2 Diabetes, highlighting the need for targeted screening and early detection in high-risk groups.